Guarani Aquifer and Patagonia. Environmental Governance from South America (1990-2017) - Manzano-Iturra, K (UNIV INDUSTRIAL SANTANDER, 2019)
Since the awakening of the first ancient cultures, water has always been a scarce good, a strategic resource, which defined the survival of people and their main activities. In South America, this situation is not different, since the unequal distribution and human activities have provoked a growing interest in water, with two geographical regions as the most relevant: the Guarani Aquifer and Patagonia. In both cases, reference is made to two reservations worldwide. Such reserves are both underground, as well as water and ice, for which the neighbouring states decided to advance the necessary agreements for their protection and use. Through this paper, it is sought to develop the concept of environmental governance by means of qualitative methodology with use of primary, secondary and tertiary sources, which will be analysed in a defined time dimension (1990-2017) and whose results show the environmental advances in the region and the treaties that have emerged over the last decades.